Kualitas Pelayanan dan Citra Perusahaan Terhadap Kepuasan Pasien Rawat Inap RS. Fatima Parepare - Ruruk, Feny; Muslimin, Ulyana; Sulawati, Sulawati (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This study aims to determine the quality of service and corporate image partially influence hospital patient satisfaction. Fatima city of Parepare. To find out the Quality of Service and Corporate Image simultaneously influence Hospital Satisfaction. Fatima city of Parepare. The analytical method used is descriptive quantitative, using primary data sourced from the results of the questionnaires that have been answered by the respondents. The tests used include validity test, reliability test, descriptive analysis, multiple linear regression analysis and t test (partial), F test (simultaneous), R2 test (coefficient of determination). The results of this study indicate that Service Quality has a partial effect on patient satisfaction with a t-count of 2.559 > 2.018 with a significant level of 0.014 < 0.05, Corporate Image has a partial effect on patient satisfaction with a t-count of 4.050 > 2.018 with a significant level of 0.000 < 0.05. Service Quality and Corporate Image simultaneously influence patient satisfaction with an F count of 38.214 > 3.22 with a significant level of 0.000 < 0.05.